First‐line therapy for chronic lymphocytic leukemia in patients older than 79 years is feasible and achieves good results: A FILO retrospective study. Issue 4 (22nd November 2016) - Meunier, Godelieve; Ysebaert, Loic; Nguyen‐Thi, Phi Linh; Lepretre, Stéphane; Quinquenel, Anne; Dupuis, Jehan; Lemal, Richard; Aurran, Thérèse; Tomowiak, Cécile; Cymbalista, Florence; Dilhuydy, Marie Sarah; Brion, Annie; et al.
Abstract: The mean age at diagnosis of chronic lymphocytic leukemia (CLL) is 72 years, with 22.8% of patients being older than 80 years. However, the elderly are underrepresented in clinical studies of CLL. We performed a retrospective study of CLL patients aged 80 years or older at the initiation of first‐line therapy in hospitals affiliated with the French intergroup on CLL (French Innovative Leukemia Organization) between 2003 and 2013. Here, we describe the clinical and biological characteristics, treatment, and outcomes for 201 patients. The median age of the cohort was 83.2 years (80–92 years). The median Cumulative Index Rating Scale comorbidity score was 5 and the median creatinine clearance was 48 mL/min (Cockcroft‐Gault formula). At treatment initiation, Binet stage was A (26.4%), B (27.9%), or C (40.3%). Therapy consisted mainly of chlorambucil (65.7%), bendamustine (10.5%), and rituximab (44.3%) as follows: chlorambucil alone (45.3%) or immunochemotherapy (48.3%) with rituximab + chlorambucil (22.7%), rituximab + bendamustine (10.4%), or rituximab + cyclophosphamide + dexamethasone (5.5%). The overall response rate was 66.2% with 31.8% clinical complete remission. The median overall and progression‐free survival from treatment initiation was 53.7 and 18.3 months, respectively. These results suggest that treatment is feasible in this age group, even with immunochemotherapy. Thus, prospective trials should target this population and oncogeriatric evaluation and new targeted therapies should be part of such future trials.